Complementary feeding among a sample of Iraqi women - Qassim, Hiba W.; Rahman, Mahmood S. A.; Aldaggistany, Zina S. A. (Scientific Journal of Medical Research, 2023)
On asking the mothers from where they obtained their information about complementary feeding, the majority of them came from family 297 mothers, who represent 74.3%, while 70 mothers (17.5 %) obtained their information from the pediatrician, while the media share only 7.2% from the sample, and at least; from friends only 1%, while trying to compare these results with other studies we found that its compatible with the result of Seema Hasnain and his colleagues, in which they found 78% of mothers obtain advice regarding complementary feeding was given by family members while in 23% mothers by doctors(32) While evaluating the types of food introduced to the infant, we classify our sample into three groups according to what they had been taken. The first group represents infants who took all the essentials ingredients, which represents the adequate feeding group which represents 81.8%; while infants who lack one essential ingredient represent the partially adequate feeding group which represents 17 %, while the non-adequate group represents only 1.2 % Our results disagree with a study conducted in India that revealed that 32% of mothers were given an adequate quantity of complementary feeds; this might be due to the difference in cultural beliefs and sample size since they took 200 infants.33 We discovered that the introduction of food did not dramatically change with age related to the mother age P value 0.466; these results seem to be similar to the results obtained by S.Rao in which he and his colleagues found that there is no statistical relation between maternal age at the time when food was first introduced (p-value 0.218).33 The mothers` educational status highly statically influences the age of food introduction to the infants since the P value was 0.0001, and these results are compatible with S. Rao and his colleague’s results. (33) We found the mother’s occupation influences the age of introduction of food since the P value is 0.003, and these results are compatible with the results of a study conducted in Pakistan by Razia Chaudry and Naheed Humayun 2007 which revealed that the mothers’ occupation is highly related to the date of food’s introduction (p-value 0.001.